Enhancing Mastery of Earth Science Concept of Prospective Physics Teachers through Interactive Conceptual Instruction Supported by Visualization and GrADS - Johan, H.; Sipriyadi, S.; Suhandi, A.; Wulan, A. R.; Herawati, A. (Jurnal Pendidikan IPA Indonesia, 2018)
Most all of earth and space science concepts are unobservable and require reasoning. Unobservable concepts have made prospective physics teachers found it hard to understand the concepts correctly. It needs visualization to help understand the concepts easily. The aim of this study was to enhance the mastery concept of earth science topic especially the earth atmosphere using interactive conceptual with visualizations and authentic data analysis with GrADS (Grid Analysis Display System). There were 23 prospective physics teachers in Bengkulu, Indonesia participated in this study. A convenience sampling technique was employed in this study. This study used pre-experimental, one group pretest-posttest design. The data were collected using pretest and posttest, questionnaires, and observation sheets. The pretest and posttest were analyzed quantitatively, while the questionnaires were analyzed qualitatively. The results showed that the prospective physics teachers’ concept mastery improved from no mastery to compete with the average normalized gain of 0.64 (medium category). 30.44% of the prospective physics teachers obtained the N-gain score in the high category and 69.56% obtained the N-gain score in the moderate category. This compilation gave them experience about the real condition of solar radiation in Indonesian atmosphere during their learning activity. It concluded that the earth science learning using interactive conceptual instruction supported by visualization and GrADS could enhance the students’ concept mastery.